Salbutamol in cardiogenic shock complicating acute myocardial infarction. - Dawson, J R (1980)
Intravenous salbutamol (13 microgram/min) has been given to 31 patients with cardiogenic shock complicating acute myocardial infarction. Haemodynamic measurements were made in nine of these patients. Salbutamol increased cardiac index by 41 per cent from 1.25 +/- 0.06 l/min per m2 to 1.76 +/- 0.19 l/min per m2 and decreased systemic vascular resistance by 16 per cent from 26.2 +/- 1.9 units to 21.9 +/- 2.1 units. Heart rate rose by 13 per cent from 95 +/- 4.5 beats/min to 106 +/- 6.0 beats/min. Pulmonary artery end-diastolic pressure fell from 20.6 +/- 1.7 mmHg to 16.9+/- 1.9 mmHg. Of the 31 patients, eight survived to leave hospital (27%). Five of the survivors had initial low heart rates and in these patients the clinical improvement was probably attributable to the positive chronotropic action of salbutamol. In the remaining three survivors clinical improvement was probably a result of salbutamol mediated afterload reduction. Salbutamol may be useful in the treatment of cardiogenic shock and pump failure complicating acute myocardial infarction.